2016
DOI: 10.1155/2016/2107027
|View full text |Cite
|
Sign up to set email alerts
|

Retention Strength after Compressive Cyclic Loading of Five Luting Agents Used in Implant-Supported Prostheses

Abstract: The purpose of this study was to evaluate and compare the retention strength of five cement types commonly used in implant-retained fixed partial dentures, before and after compressive cyclic loading. In five solid abutments screwed to 5 implant analogs, 50 metal Cr-Ni alloy copings were cemented with five luting agents: resin-modified glass ionomer (RmGI), resin composite (RC), glass ionomer (GI), resin urethane-based (RUB), and compomer cement (CC). Two tensile tests were conducted with a universal testing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that compressive cycling loading significantly reduces the dislodging force after cementation is complete. 31 32 However, this study proceeded only for thermal cycling between cold and hot baths after cementation, and the role of cycling loading to the cemented crowns could not be evaluated. Furthermore, if a compressive cyclic loading test was to be performed for this research, the rounded or curved upper part of the crown could have been an obstacle to receive an evenly distributed compressive force.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that compressive cycling loading significantly reduces the dislodging force after cementation is complete. 31 32 However, this study proceeded only for thermal cycling between cold and hot baths after cementation, and the role of cycling loading to the cemented crowns could not be evaluated. Furthermore, if a compressive cyclic loading test was to be performed for this research, the rounded or curved upper part of the crown could have been an obstacle to receive an evenly distributed compressive force.…”
Section: Discussionmentioning
confidence: 99%
“…34 The adopted thermo cycling protocol in this study simulated 2.5 years of clinical service, 29 while the cyclic loading protocol simulated 2-3 months of clinical service. 31 Also, water has been suggested to play a role in the propagation of small cracks. Thus, we used deionized water instead of artificial saliva, since it has no significant effect on the coefficient of friction between natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Using deionized water, 100,000 cycles were applied with a load of 100 N and a frequency of 1 Hz, corresponding to 2-3 months of clinical service. 30,31…”
Section: Simulation Of Oral Conditionsmentioning
confidence: 99%
“…Implant-abutment connection and retention type (cemented or screw retained) are critical factors for the long-term success of ISFP (Implant supported fixed prosthesis) (1). Despite the disadvantages of cement-retained restorations such as peri-implantitis, peri-implant mucositis, and difficulties in removing for future maintenance, cemented ORIGINAL ARTICLE / ÖZGÜN ARAŞTIRMA restorations are still commonly used in clinical practice due to less mechanical complication, easy production, esthetics, and lower costs (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the retention of restorations depends on type of cement, axio-occlusal angle, composition of crown material and texture, abutment height and firstly frictional retention (3). In clinical practice, cement-retained restorations should exhibit easy retrievability and adequate retention strength to avoid decementation (1). Zinc phosphate, zinc polycarboxylate, glass-ionomer, and self-cure resin cements have been commonly selected for the permanent cementation of ISFP (12).…”
Section: Introductionmentioning
confidence: 99%